Effects of Inquiry and Cooperative Learning Models on Volleyball Smash Skills: An Experimental Study of FKIP Physical Education Students - Syaiful, Andi; Ince Abdul Muhaemin; Marsuki; Nurwahidin Hakim, (Musamus Journal of Physical Education and Sport (MJPES), 2026)
Objectives. This study looked at how the inquiry learning model and the cooperative learning model affect volleyball smash ability in FKIP Physical Education (Penjaskesrek) students, and which of the two gives better learning results.Materials and Methods. The study used an experimental pretest–posttest design with two groups. A total of 40 FKIP Physical Education students took part and were split into two groups: 20 students followed the inquiry learning model and 20 students followed the cooperative learning model. Smash ability was assessed using a standardized volleyball smash test before and after the program. The intervention ran for six weeks during regular volleyball classes. Data were processed with descriptive statistics, normality and homogeneity tests, and paired as well as independent sample t-tests, using a significance level of 0.05.Results. Both groups improved after the treatment. In the inquiry group, the mean score increased from 68.40 (pretest) to 78.75 (posttest). In the cooperative group, the mean score rose from 67.95 to 83.20. The t-test showed that the improvements in both groups were significant (p < 0.05). Even so, the cooperative group gained more overall and showed a stronger difference than the inquiry group.Conclusions. Both inquiry and cooperative learning helped students improve their volleyball smash ability. However, cooperative learning led to better progress. The group-based practice, peer feedback, and shared roles in cooperative sessions likely made it easier for students to refine technique and reach skill mastery during training.